Porous polybenzimidazole / proton conductor type polyamide composite ionic membrane as well as preparation method and application thereof
By combining proton-conductive polyamide with polybenzimidazole and triethanolamine to form a porous composite ion membrane, the problems of low proton conductivity and insufficient acid retention of traditional ion membranes under high temperature and high pressure conditions are solved, and higher proton conductivity and acid absorption capacity are achieved. It is suitable for high-temperature hydrogen fuel cells and vanadium flow batteries.
Patent Information
- Application Number
- CN202411561224.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, traditional perfluorosulfonic acid ion membranes exhibit problems such as low proton conductivity and insufficient acid retention under high temperature and high pressure conditions, which limits their application in hydrogen fuel cells and vanadium flow batteries.
A porous composite ion film combining proton conductor polyamide and polybenzimidazole is used to form a proton conductor polyamide by polymerizing diamine monomer and dicarboxylic acid monomer, and mixed with polybenzimidazole and triethanolamine to form a uniform system and then cast into a film. The pore-forming agent is soaked in the acid solution to obtain a porous polybenzimidazole/proton conductor polyamide composite ion film.
It improves the intrinsic proton conductivity of the ion membrane, enhances the acid absorption capacity, ensures airtightness and high-resistance vanadium performance, and is suitable for hydrogen fuel cells and vanadium flow battery applications under high temperature and high pressure conditions.
Smart Images

Figure CN119518045A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer electrolyte membranes, and specifically relates to a porous polybenzimidazole / proton conductor type polyamide composite ion membrane, a preparation method and application thereof, in particular to applications in hydrogen fuel cells and vanadium liquid flow batteries. Background Art
[0002] Ion membranes are widely used in hydrogen fuel cells, vanadium flow batteries and other fields because they can conduct certain specific ions, such as protons. The application temperature of traditional perfluorosulfonic acid (nafion) ion membranes in the field of fuel cells should be lower than 100°C, and the scope of use is severely limited; in the field of flow batteries, due to its poor vanadium resistance, its coulomb efficiency is low. These disadvantages seriously affect the application scope of perfluorosulfonic acid membranes. Polybenzimidazole ion membranes are cheaper and can cope with high temperatures of 180°C and above in fuel cells. They show ultra-high vanadium resistance in the field of vanadium flow batteries, making them an excellent product that fully replaces perfluorosulfonic acid ion membranes. However, polybenzimidazole ion membranes will exhibit problems such as low proton conductivity and insufficient acid retention, which are challenged in applications such as hydrogen fuel cells and vanadium flow batteries.
[0003] Based on the above reasons, this application is filed. Summary of the invention
[0004] Based on the above reasons, in view of the problems or defects in the prior art, the purpose of the present invention is to provide a porous polybenzimidazole / proton conductor type polyamide composite ion membrane, its preparation method and application, to solve or at least partially solve the above technical defects in the prior art: the proton conductor type polyamide synthesized by the present invention has a certain proton conductivity, and adding it to the polybenzimidazole ion membrane can improve the intrinsic proton conductivity of the ion membrane, rather than relying more on the adsorption of acid (including phosphoric acid, sulfuric acid, etc.). In addition, the addition of the triethanolamine pore-forming agent of the present invention can form a tiny and unconnected porous structure inside the ion membrane, and obtain higher acid absorption and thus higher proton conductivity under the premise of ensuring the air tightness and high vanadium resistance of the ion membrane.
[0005] In order to achieve one of the above purposes of the present invention, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a porous polybenzimidazole / proton conductor polyamide composite ion membrane comprises the following steps: blending proton conductor polyamide with polybenzimidazole and an organic solvent to form a uniform system; then adding an organic pore-forming agent and casting a volatile solvent to form a membrane; and finally soaking the membrane in an acid solution to obtain the porous polybenzimidazole / proton conductor polyamide composite ion membrane.
[0007] Furthermore, in the above technical solution, the proton conductor polyamide is produced by polymerization of a diamine monomer and a dicarboxylic acid monomer; wherein: the diamine monomer or the dicarboxylic acid monomer combination can be: a combination of a diamine monomer having a proton conductor group and a dicarboxylic acid monomer without a proton conductor group; a combination of a diamine monomer without a proton conductor group and a dicarboxylic acid monomer having a proton conductor group; or at least one combination of a diamine monomer having a proton conductor group and a dicarboxylic acid monomer having a proton conductor group.
[0008] Further, in the above technical solution, the diamine monomer having a proton conductor group contains one or more proton conductors. In a preferred embodiment of the present invention, the diamine monomer having a proton conductor group can be one or a mixture of 4,4-diaminobisbenzenesulfonyl imide, 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, p-phenylenediamine-2,5-disulfonic acid, and benzidine disulfonic acid.
[0009] Furthermore, in the above technical solution, the dicarboxylic acid monomer without proton conductor group does not contain proton conductor. In a preferred embodiment of the present invention, the dicarboxylic acid monomer without proton conductor group can be one or a mixture of terephthalic acid, isophthalic acid, diphenyl ether dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, ferrocene dicarboxylic acid, 4,4-sulfonyl dibenzoic acid, 2,2-bis(4-carboxyphenyl)hexafluoropropane.
[0010] Furthermore, in the above technical solution, the dicarboxylic acid monomer having a proton conductor group contains one or more proton conductors. In a preferred embodiment of the present invention, the dicarboxylic acid monomer having a proton conductor group can be one or a mixture of several of 4,4-dicarboxybisbenzenesulfonimide, 5-sulfoisophthalic acid, and 2-sulfonate terephthalic acid.
[0011] Furthermore, in the above technical solution, the diamine monomer without proton conductor groups does not contain a proton conductor. In a preferred embodiment of the present invention, the diamine monomer without proton conductor groups can be one or a mixture of hexamethylenediamine, p-phenylenediamine, 1,5-diaminonaphthalene, 4,4-diaminodiphenyl sulfone, bis(4-aminophenyl)sulfide, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-(ethylenedioxy)bis(ethylamine).
[0012] Furthermore, in the above technical solution, the proton conductor type polyamide is prepared by the following method:
[0013] The diamine monomer, the dicarboxylic acid monomer and anhydrous lithium chloride are dissolved in a mixed solvent in sequence, and then the obtained mixed reaction system is heated to 100° C. and stirred at a constant temperature for 2 to 12 hours under an inert atmosphere; after the reaction, the obtained product is precipitated with alcohol, and then filtered, washed and dried to obtain the proton conductor polyamide.
[0014] Furthermore, in the above technical solution, the molar ratio of the diamine monomer to the dicarboxylic acid monomer is 1:1.
[0015] Furthermore, in the above technical solution, the mixed solvent consists of 1-methyl-2-pyrrolidone, pyridine and triphenyl phosphite.
[0016] Preferably, in the above technical solution, the volume ratio of 1-methyl-2-pyrrolidone, pyridine and triphenyl phosphite is 4:3:1.
[0017] Preferably, in the above technical solution, the usage ratio of the anhydrous lithium chloride to the mixed solvent is 3.75g:100mL.
[0018] Preferably, in the above technical solution, the usage ratio of the diamine monomer to the mixed solvent is 0.02 mol: (50-100) mL.
[0019] Furthermore, in the above technical solution, in a preferred embodiment of the present invention, the organic pore-forming agent is triethanolamine.
[0020] Further, in the above technical solution, the organic solvent includes one or a mixture of N,N-dimethylformamide, N,N-dimethylacetamide, 1-methyl-2-pyrrolidone, dimethyl sulfoxide, trifluoroacetic acid, methanesulfonic acid, and formic acid. The amount of the organic solvent used is not specifically limited, as long as the proton conductor polyamide, polybenzimidazole, and organic pore-forming agent can be uniformly and completely dissolved.
[0021] Furthermore, in the above technical solution, the mass ratio of the proton conductor polyamide, polybenzimidazole and triethanolamine is 4-57:22-63:14-58.
[0022] Further, in the above technical solution, the polybenzimidazole comprises a mixture of one or more repeating units of the following formula: wherein n is 1 or greater, about 10 or greater, or about 100 or greater;
[0023]
[0024]
[0025] Furthermore, in the above technical solution, the method for preparing the porous polybenzimidazole / proton conductor type polyamide composite ion membrane comprises the following steps:
[0026] S1 polymerizing the diamine monomer and the dicarboxylic acid monomer to generate a proton conductor type polyamide;
[0027] S2: mixing the proton conductor polyamide with polybenzimidazole, an organic pore-forming agent, and an organic solvent, dissolving the mixture, and obtaining a polybenzimidazole membrane solution;
[0028] S3: coating the polybenzimidazole membrane solution on a smooth substrate to obtain a polybenzimidazole / proton conductor type polyamide composite ion membrane;
[0029] S4: immersing the polybenzimidazole / proton conductor type polyamide composite ion membrane in an acid solution to remove the organic pore-forming agent, thereby obtaining the porous polybenzimidazole / proton conductor type polyamide composite ion membrane.
[0030] Preferably, in the above technical solution, the acid in the acid solution includes one or a mixture of sulfuric acid, hydrochloric acid, nitric acid, bistrifluoromethylsulfonimide, formic acid, and acetic acid.
[0031] Preferably, in the above technical solution, the molar concentration of the acid in the acid solution is 0.1M to 5M.
[0032] The second object of the present invention is to provide a porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared by the above method.
[0033] Furthermore, in the above technical solution, the thickness of the polybenzimidazole / proton conductor polyamide composite ion membrane is 5 to 100 microns.
[0034] The third object of the present invention is to provide the use of the porous polybenzimidazole / proton conductor polyamide composite ion membrane prepared by the above method in hydrogen fuel cells and vanadium liquid flow batteries.
[0035] The present invention also provides a hydrogen fuel cell or a vanadium liquid flow battery, comprising a porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared by the method of the present invention.
[0036] The mechanism involved in the present invention is as follows:
[0037] The present invention introduces polyamide with proton conductor, which itself has certain proton conductivity, and improves the intrinsic proton conductivity of the composite ion membrane without being affected by the amount of acid absorption.
[0038] The present invention introduces triethanolamine pore-forming agent, which can form tiny and unconnected porous structures in the ion membrane after being leached by acid, thereby obtaining higher acid absorption under the premise of ensuring the air tightness and high vanadium resistance of the ion membrane, and synergistically acting with the proton conductor polyamide to jointly improve the proton conductivity of the ion membrane.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] ① The proton conductivity of the porous polybenzimidazole / proton conductor polyamide composite ion membrane provided by the present invention in a hydrogen fuel cell is less affected by the amount of phosphoric acid adsorbed, and can be used at high temperatures exceeding 180°C and low phosphoric acid adsorption amounts with a mass fraction of less than 200%.
[0041] ② The proton conductivity of the porous polybenzimidazole / proton conductor polyamide composite ion membrane provided by the present invention in the vanadium flow battery is higher than that of most polybenzimidazole-based ion membranes. At the same time, due to its excellent vanadium resistance performance, the coulombic efficiency, voltage efficiency and energy efficiency of the flow battery all reach a relatively high level.
[0042] ③ The preparation method of the porous polybenzimidazole / proton conductor type polyamide composite ion membrane provided by the present invention is simple, and the polyamide with proton conductor is formed by one-step polymerization, and then mixed with polybenzimidazole and triethanolamine pore-forming agent, dissolved and dispersed to form a uniform system, and then cast into a membrane, and finally a porous ion membrane is obtained after washing with acid solution. The prepared ion membrane has excellent intrinsic physical properties such as heat resistance, mechanical strength, and antioxidant stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 A physical picture of the porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared in Example 1-3 of the present invention;
[0045] Figure 2 The stress-strain curve diagram of the porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared in Examples 1-3 of the present invention;
[0046] Figure 3 The conductivity variation diagram of the porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared in Examples 1-3 of the present invention when applied to a hydrogen fuel cell at different temperatures;
[0047] Figure 4 The Nyquist plot of the porous polybenzimidazole / proton conductor polyamide composite ion membrane prepared in Examples 1-3 of the present invention applied to vanadium redox flow batteries;
[0048] Figure 5 This is the hydrogen nuclear magnetic resonance spectrum of the proton conductor polyamide material prepared in Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0049] The present invention discloses a porous polybenzimidazole / proton conductor type polyamide composite ion membrane, a preparation method and application thereof, wherein the preparation process comprises the following steps: ① polymerizing a diamine monomer and a dicarboxylic acid monomer to generate a proton conductor type polyamide; ② mixing and dissolving the proton conductor type polyamide with polybenzimidazole, triethanolamine and an organic solvent to obtain a polybenzimidazole membrane liquid; ③ coating the polybenzimidazole membrane liquid on a smooth substrate to obtain a polybenzimidazole / proton conductor type polyamide composite ion membrane; ④ immersing the polybenzimidazole / proton conductor type polyamide composite ion membrane in an acid solution to remove an organic pore-forming agent to obtain the membrane. The method of the present invention has a simple operation process, and the prepared ion membrane has very excellent proton conductivity and intrinsic physical properties.
[0050] The amount of each solid sample added in the examples of the present invention is based on the purity reference provided by the original manufacturer.
[0051] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.
[0052] The 4,4-dicarboxy bisbenzenesulfonyl imide, referred to as CBSI, used in the following embodiments of the present invention is synthesized according to the method of bis(4-carbonylbenzenesulfonyl)imide (CBSI) disclosed in Example 1 of the authorized patent CN 111081946 B (application date: 2019-12-25), and belongs to the material disclosed in the prior art.
[0053] The aromatic ether polybenzimidazole (OPBI) involved in the following embodiments of the present invention is synthesized by the method of Example 4 in the patent publication number CN116063679 B. The specific method is as follows:
[0054] (1) Add 3.90 g of phosphorus pentoxide to 25 mL of methanesulfonic acid (CAS No.: 75-75-2), heat at 120° C. with magnetic stirring for 5 h, dissolve and cool to room temperature to obtain a phosphorus pentoxide / methanesulfonic acid solution;
[0055] Add 20 mL of the pre-prepared phosphorus pentoxide / methanesulfonic acid solution to a 100 mL round-bottom flask, heat and stir to 40° C. under nitrogen protection; accurately weigh 5 mmol each of 4,4'-dicarboxy diphenyl ether and 3,3'-diaminobenzidine (the corresponding masses of both monomers are calculated based on the purity) and add them to the phosphorus pentoxide / methanesulfonic acid solution; stir and mix thoroughly to obtain a reaction precursor;
[0056] (2) transferring the reaction precursor to a microwave synthesizer, heating it under a microwave of a certain power, setting relevant program parameters for temperature increase reaction, and the reaction is carried out in two stages: first, the temperature is raised to 120° C. for reaction for 30 min, and then the temperature is raised to 150° C. for reaction for 20 min, and the microwave power is 500 W;
[0057] (3) After the reaction is completed, when the temperature of the reaction liquid drops to about 80° C., the reaction liquid is slowly poured into a glass beaker containing deionized water, the precipitated polymer is washed with water until it is nearly neutral, and then a saturated sodium bicarbonate solution is added for neutralization, and the mixture is filtered under reduced pressure, first washed with water for multiple times, and then washed with ethanol for multiple times, and the obtained polymer is vacuum dried at 120° C. for 24 hours, and ground into powder, i.e., the aromatic ether type polybenzimidazole.
[0058] The meta-fully aromatic polybenzimidazole (mPBI) involved in the following embodiments of the present invention is synthesized by the method of Example 3 in the patent with authorization announcement number CN 116063679 B. The specific method is as follows:
[0059] (1) Add 3.85 g of phosphorus pentoxide to 25 mL of methanesulfonic acid (CAS No.: 75-75-2), heat with magnetic stirring at 120° C. for 5 h, and cool to room temperature after dissolving to obtain a phosphorus pentoxide / methanesulfonic acid solution;
[0060] Add 20 mL of the pre-prepared phosphorus pentoxide / methanesulfonic acid solution to a 100 mL round-bottom flask, heat and stir to 40° C. under nitrogen protection; accurately weigh 5 mmol of isophthalic acid and 3,3'-diaminobenzidine (the corresponding masses of both monomers are calculated based on their purity) and add them to the phosphorus pentoxide / methanesulfonic acid solution; stir and mix thoroughly to obtain a reaction precursor;
[0061] (2) transferring the reaction precursor to a microwave synthesizer, heating it under a certain power of microwave, setting relevant program parameters for temperature rise reaction, and the reaction is carried out in two stages: first, the temperature is raised to 120° C. for reaction for 20 min, and then the temperature is raised to 160° C. for reaction for 40 min, and the microwave power is 300 W;
[0062] (3) After the reaction is completed, when the temperature of the reaction liquid drops to about 80° C., the reaction liquid is slowly poured into a glass beaker containing deionized water, the precipitated polymer is washed with water until it is nearly neutral, and then a saturated sodium bicarbonate solution is added for neutralization, and the mixture is filtered under reduced pressure, first washed with water for multiple times, and then washed with ethanol for multiple times, and the obtained polymer is vacuum dried at 120° C. for 24 hours, and ground into powder to obtain the meta-aromatic polybenzimidazole.
[0063] Example 1
[0064] A method for preparing a porous polybenzimidazole / proton conductor type polyamide composite ion membrane of this embodiment comprises the following steps:
[0065] ① Take 4.97g of 4,4-diaminodiphenyl sulfone, 7.71g of 4,4-dicarboxybisbenzenesulfonimide (CBSI) (the molar ratio of the two is 1:1), and 3g of anhydrous lithium chloride and dissolve them in a mixed solvent consisting of 40mL 1-methyl-2-pyrrolidone, 30mL pyridine and 10mL triphenyl phosphite. Then heat the resulting mixed reaction system to 100℃ and stir the reaction at a constant temperature for 12h under a nitrogen atmosphere. Pour the mixed solution after the reaction into methanol under stirring, and the product is a white precipitate. Filter the white precipitate and wash it several times with methanol and ultrapure water. Filter and collect the product and dry it at 80℃ for 12h to obtain a proton conductor polyamide.
[0066] ② Take 0.2g of the proton conductor polyamide obtained above, mix it with 2g of aromatic ether polybenzimidazole (OPBI), dissolve it in a mixed solution of 20ml N,N-dimethylformamide containing 2g of triethanolamine, heat it to 100℃ and stir it at constant temperature for 12h to obtain a viscous membrane liquid.
[0067] ③ The above membrane liquid was cast on a smooth substrate to obtain a pre-ion membrane with a thickness of 38 microns.
[0068] ④ After peeling off the front ion membrane from the substrate, place it in 3M dilute sulfuric acid for up to 12 hours, take it out and rinse it with deionized water to obtain a porous polybenzimidazole / proton conductor polyamide composite ion membrane.
[0069] Example 2
[0070] A method for preparing a porous polybenzimidazole / proton conductor type polyamide composite ion membrane of this embodiment comprises the following steps:
[0071] ① Take 6.69g of 2,2-bis(4-aminophenyl)hexafluoropropane, 7.71g of 4,4-dicarboxybisbenzenesulfonimide (CBSI) (molar ratio of 1:1), and 3g of anhydrous lithium chloride and dissolve them in a mixed solvent consisting of 40mL of 1-methyl-2-pyrrolidone, 30mL of pyridine and 10mL of triphenyl phosphite. Then heat the resulting mixed reaction system to 100°C and stir the reaction at a constant temperature for 12h under a nitrogen atmosphere. Pour the mixed solution after the reaction into methanol under stirring, and the product is a white precipitate. Filter the white precipitate and wash it several times with methanol and ultrapure water. Filter and collect the product and dry it at 80°C for 12h to obtain a polyamide with a proton conductor.
[0072] ② Take 0.5g of the above-mentioned proton conductive polyamide, mix it with 2g of meta-aromatic polybenzimidazole (mPBI) and dissolve it in a mixed solution of 20ml N,N-dimethylformamide containing 2g of triethanolamine, heat it to 100℃ and stir it at constant temperature for 12h to obtain a viscous membrane liquid.
[0073] ③ The above membrane liquid was cast on a smooth substrate to obtain a pre-ion membrane with a thickness of 42 microns.
[0074] ④ After peeling off the front ion membrane from the substrate, place it in 3M dilute sulfuric acid for up to 12 hours, take it out and rinse it with deionized water to obtain a porous polybenzimidazole / proton conductor polyamide composite ion membrane.
[0075] Example 3
[0076] A method for preparing a porous polybenzimidazole / proton conductor type polyamide composite ion membrane of this embodiment comprises the following steps:
[0077] ① Take 4.97g of 4,4-diaminodiphenyl sulfone, 7.71g of 4,4-dicarboxybisbenzenesulfonimide (CBSI) (molar ratio of 1:1), and 3g of anhydrous lithium chloride and dissolve them in a mixed solvent consisting of 40mL of 1-methyl-2-pyrrolidone, 30mL of pyridine and 10mL of triphenyl phosphite. Then heat the resulting mixed reaction system to 100°C and stir the reaction at a constant temperature for 12h under a nitrogen atmosphere. Pour the mixed solution after the reaction into methanol under stirring, and the product obtained is a white precipitate. Filter the white precipitate and wash it several times with methanol and ultrapure water. Filter and collect the product and dry it at 80°C for 12h to obtain a proton conductor polyamide.
[0078] ② Take 1g of the above-mentioned proton conductor polyamide and 2g of mixed polybenzimidazole (wherein the mass ratio of mPBI to OPBI is 1:1) and dissolve them in 20ml of N,N-dimethylformamide mixed solution containing 1.5g of triethanolamine, heat to 100℃ and stir at constant temperature for 12h to obtain a viscous membrane liquid.
[0079] ③ The above membrane liquid was cast on a smooth substrate to obtain a pre-ion membrane with a thickness of 39 microns.
[0080] ④ After peeling off the front ion membrane from the substrate, place it in 3M dilute sulfuric acid for up to 12 hours, take it out and rinse it with deionized water to obtain a porous polybenzimidazole / proton conductor polyamide composite ion membrane.
[0081] Performance Testing:
[0082] (I) The test methods for mechanical properties are as follows:
[0083] ① Under constant temperature and humidity conditions of 25℃±2℃ and 50%±5%, quickly measure the thickness of the sample. The thickness and width of each sample should be measured at three points within the gauge length and the average value should be taken. The thickness measurement accuracy is ±0.2% and the width measurement accuracy is ±0.5%;
[0084] ②Place the sample in the test fixture of the tensile testing machine, make the longitudinal axis of the sample coincide with the center line of the upper and lower fixtures, and clamp it. The pressure value of the pneumatic fixture is set to 5.3MPa;
[0085] ③The tensile speed of the tensile testing machine is set at 100 mm / min -1 ;
[0086] ④After the sample breaks, read the corresponding load value. If the sample breaks outside the marked line, the test is invalid.
[0087] The required load and the corresponding film thickness and width are read according to the measured tensile curve, and the maximum tensile strength of the film is calculated according to the formula.
[0088]
[0089] Where:
[0090] P——The maximum tensile strength of the film, in megapascals (MPa);
[0091] F——maximum load, in Newton (N);
[0092] b——specimen width, in millimeters (mm);
[0093] d——specimen thickness, in millimeters (mm).
[0094] Take 3 samples as a group and calculate the average value as the test result.
[0095] (II) The test method for antioxidant stability is as follows:
[0096] The antioxidant stability test method involved in the present invention is carried out with reference to the "Fenton reagent oxidation method" in Summary 5.11 "Antioxidant performance" of NB / T42028-2023. The detailed test method is as follows:
[0097] ① Use 30% hydrogen peroxide solution opened within one month and dilute it to prepare 3% hydrogen peroxide solution. Take 50ml of the above 3% hydrogen peroxide solution and add 0.1ml of 0.1M ferrous sulfate solution to obtain Fenton's reagent. Make sure that the Fenton's reagent is prepared and used immediately.
[0098] ②Cut the pre-treated membrane fragment 25cm 2 , place it in a vacuum drying oven at 110℃ for 2h, dry it until the difference between the two weighings is less than 0.2mg, and weigh its mass on a balance as m0;
[0099] ③ Cut the dried membrane fragments into pieces and put them into a beaker, add the prepared Fenton reagent to ensure that the membrane is completely immersed, and then keep the beaker at 60℃ for 3h;
[0100] ④ Take out the membrane and put it into a beaker filled with 3M dilute sulfuric acid aqueous solution. After soaking for 30 minutes, rinse the membrane sample with deionized water until the pH value of the water after washing is neutral. Then place the rinsed membrane in a vacuum drying oven at 110℃ for 2 hours and dry it until the difference between the two weighings is less than 0.2mg. Weigh its mass with a balance as m a ;
[0101] The antioxidant properties of the membrane are characterized by comparing the mass changes of the dried membrane before and after the Fenton reagent treatment according to the formula. The larger the value, the more serious the degradation of the polymer membrane during the Fenton reagent treatment, and the worse the antioxidant properties of the membrane. The antioxidant coefficient is represented by S.
[0102]
[0103] Where:
[0104] S——Antioxidation coefficient measured by Fenton reagent oxidation method, characterized by mass change;
[0105] m0——the mass of the dried membrane before Fenton's reagent treatment;
[0106] m a ——The quality of the dried membrane after treatment with Fenton's reagent.
[0107] (III) The specific test method for proton conductivity of hydrogen fuel cells is as follows:
[0108] The proton conductivity test method involved in the present invention refers to Section 3.5 "Proton conductivity test" in GB / T20042.3-2009. The detailed test method is as follows:
[0109] Cut a film of a certain size as a sample, measure the thickness of the sample with a thickness gauge at a temperature of 25℃±2℃ and a relative humidity of 50±5%, and take the average value of three points as the value for calculating the thickness d. Fix the sample in the conductivity measurement fixture, and tighten the bolts with a torque wrench at a torque of 3Nm. Then place the conductivity measurement fixture in different temperature and constant humidity environments, and test it after keeping it constant for 30 minutes under each temperature and humidity condition. 6 The impedance spectrum of the sample was measured by an electrochemical impedance tester under the conditions of 100 Hz and a disturbance voltage of 10 mV. In the measured impedance spectrum, the impedance value (R) of the sample was read from the intersection of the high-frequency part of the spectrum line and the real axis, and the proton conductivity of the sample was calculated according to the following formula:
[0110]
[0111] Where:
[0112] σ——proton conductivity of the sample, in millisiemens per centimeter (mScm -1 );
[0113] a——the distance between the two electrodes, in centimeters (cm);
[0114] R——Measurement impedance of the sample, in kilo-ohms (kΩ);
[0115] b——The effective length of the membrane in the direction perpendicular to the electrode, in centimeters (cm);
[0116] d is the thickness of the sample in centimeters (cm).
[0117] Take 3 samples as a group and calculate the average value as the test result.
[0118] (IV) The test methods for proton conductivity and surface resistance of vanadium liquid flow battery are as follows:
[0119] The test method for surface resistance and proton conductivity involved in the present invention refers to Section 5.7 "Conductivity and membrane resistance" in NB / T42028-2023. The detailed test method is as follows:
[0120] ① Cut the membrane into 3cm×3cm square pieces and immerse them in 3M sulfuric acid solution for 24h, which is called membrane pretreatment;
[0121] ②Join the two half slots of the conductivity cell, press them tightly with an iron clamp, use a dropper to add 3M sulfuric acid solution to the liquid adding hole of the conductivity cell and expel the bubbles. The liquid level should be higher than the circular hole of the half slot;
[0122] ③ Clamp the counter electrode and reference electrode test wires of the electrochemical workstation to the electrode at one end of the conductivity cell, and clamp the working electrode test wire to the electrode at the other end of the conductivity cell, and measure the impedance of the conductivity cell. After the test is completed, read the resistance value in the high-frequency region that intersects the real axis, which is the blank impedance R1 of the conductivity cell.
[0123] ④ Clamp the pretreated membrane sample between the two half-groove circular holes, repeat step ③, and read the data, which is the impedance R2 of the conductivity cell with the membrane sample installed;
[0124] ⑤ Repeat the measurement 3 times, record all impedance data and calculate the average value, which is recorded as Calculated according to the following formula:
[0125]
[0126] In the formula
[0127] R2——The impedance value of the conductivity cell with the membrane sample installed, in ohms (Ω);
[0128] R1——The impedance value of the conductivity cell without the membrane sample installed, in ohms (Ω);
[0129] R A ——Film surface resistance, in ohm square centimeter (Ωcm 2 );
[0130] A——The effective area of the membrane, in square centimeters (cm 2 );
[0131]
[0132] In the formula
[0133] σ——proton conductivity of the sample, in Siemens per centimeter (Scm -1 );
[0134] d——average thickness of the film, in centimeters (cm);
[0135] Take 3 samples as a group and take the average value as the test result.
[0136] Test results analysis
[0137] Figure 1This is a physical picture of the porous polybenzimidazole / proton conductor polyamide composite ion membrane prepared in Examples 1-3 of the present invention, showing that polybenzimidazole and proton conductor polyamide have good compatibility, no phase separation phenomenon occurs, and the film-forming property is excellent.
[0138] Figure 2 The stress-strain curves of the porous polybenzimidazole / proton conductor type polyamide composite ion membranes prepared in Examples 1-3 of the present invention are shown in this figure. The mechanical strength of the composite ion membrane prepared in Example 1 of the present invention reaches 122MPa, which meets the use requirements; the mechanical strength of the composite ion membrane prepared in Example 2 of the present invention can reach 116MPa, which meets the use requirements; the mechanical strength of the composite ion membrane prepared in Example 3 of the present invention can reach 121MPa, which meets the use requirements.
[0139] Table 1 is a table showing the antioxidant stability of the porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared in Examples 1-3 of the present invention using the Fendon reagent method.
[0140] Table 1
[0141]
[0142] Table 1 is a list of the antioxidant stability of the porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared in Examples 1-3 of the present invention by the Fendon reagent method. This table shows that the antioxidant coefficient of the composite ion membrane prepared in Example 1 of the present invention is 1.17%, which meets the use requirements; the antioxidant coefficient of the composite ion membrane prepared in Example 2 of the present invention is 0.61%, which meets the use requirements; the antioxidant coefficient of the composite ion membrane prepared in Example 3 of the present invention is 0.75%, which meets the use requirements.
[0143] Figure 3 The conductivity change diagram of the porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared in Examples 1-3 of the present invention under different temperatures for use in hydrogen fuel cells. This figure shows that the optimum temperature conductivity of the composite ion membrane prepared in Example 1 of the present invention is 136 mScm -1 , reaching a relatively high level in the industry; the optimum temperature conductivity of the composite ion membrane prepared in Example 2 of the present invention is 133mScm -1 , reaching a relatively high level in the industry; the optimum temperature conductivity of the composite ion membrane prepared in Example 3 of the present invention is 147mScm -1 , reaching a relatively high level in the industry.
[0144] Figure 4The conductivity change diagram of the porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared in Examples 1-3 of the present invention under different temperatures for use in vanadium redox flow batteries. According to this diagram, it is calculated that the surface resistance of the composite ion membrane prepared in Example 1 of the present invention is 0.686Ωcm 2 , reaching a relatively high level in the industry; the surface resistance of the composite ion membrane prepared in Example 2 of the present invention is 0.592Ωcm 2 , reaching a relatively high level in the industry; the surface resistance of the composite ion membrane prepared in Example 3 of the present invention is 0.684Ωcm 2 , reaching a relatively high level in the industry.
[0145] Figure 5 This is the nuclear magnetic resonance hydrogen spectrum of the proton conductor polyamide material prepared in Examples 1-3 of the present invention. This figure shows that the proton conductor polyamide prepared in Examples 1 and 3 of the present invention has obvious chemical shift peaks at 10.5ppm, 8.3ppm, 8.2ppm, 7.4ppm, 7.3ppm, and 7.2ppm, proving that the proton conductor polyamide whose reactants are 4,4-diaminodiphenyl sulfone and 4,4-dicarboxy bisbenzenesulfonimide is synthesized; the proton conductor polyamide prepared in Example 2 of the present invention has obvious chemical shift peaks at 10.7ppm, 8.1ppm, 7.9ppm, 7.7ppm, 7.6ppm, and 7.2ppm, proving that the proton conductor polyamide whose reactants are 2,2-bis(4-aminophenyl)hexafluoropropane and 4,4-dicarboxy bisbenzenesulfonimide is synthesized.
[0146] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a porous polybenzimidazole / proton conductor type polyamide composite ion membrane, characterized in that: Specifically, proton conductor polyamide is blended with polybenzimidazole and organic solvent to form a uniform system, then an organic pore-forming agent is added and a volatile solvent is poured to form a film, and finally the porous polybenzimidazole / proton conductor polyamide composite ion membrane is obtained after being soaked in acid solution.
2. The preparation method according to claim 1, characterized in that: The proton conductor type polyamide is produced by polymerization of a diamine monomer and a dicarboxylic acid monomer; wherein: the diamine monomer or the dicarboxylic acid monomer combination can be: a combination of a diamine monomer having a proton conductor group and a dicarboxylic acid monomer without a proton conductor group; a combination of a diamine monomer without a proton conductor group and a dicarboxylic acid monomer having a proton conductor group; or at least one combination of a diamine monomer having a proton conductor group and a dicarboxylic acid monomer having a proton conductor group.
3. The preparation method according to claim 2, characterized in that: The diamine monomer having a proton conductor group contains one or more proton conductors, which are one or a mixture of 4,4-diaminobisbenzenesulfonyl imide, 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, p-phenylenediamine-2,5-disulfonic acid, and benzidine disulfonic acid.
4. The preparation method according to claim 2, characterized in that: The dicarboxylic acid monomer having a proton conductor group contains one or more proton conductors, and is one or a mixture of 4,4-dicarboxybisbenzenesulfonimide, 5-sulfoisophthalic acid, and 2-sulfoterephthalic acid.
5. The preparation method according to claim 2, characterized in that: The proton conductor type polyamide is prepared by the following method: The diamine monomer, the dicarboxylic acid monomer and anhydrous lithium chloride are dissolved in a mixed solvent in sequence, and then the obtained mixed reaction system is heated to 100° C. and stirred at a constant temperature for 2 to 12 hours under an inert atmosphere; after the reaction, the obtained product is precipitated with alcohol, and then filtered, washed and dried to obtain the proton conductor polyamide.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the proton conductor type polyamide, polybenzimidazole and triethanolamine is 4-57:22-63:14-58.
7. The preparation method according to claim 1, characterized in that: The polybenzimidazole comprises one or a mixture of the following repeating units:
8. The porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared by the preparation method according to any one of claims 1 to 7.
9. Application of the porous polybenzimidazole / proton conductor polyamide composite ion membrane prepared by the preparation method according to any one of claims 1 to 7 in hydrogen fuel cells and vanadium liquid flow batteries.
10. A hydrogen fuel cell or a vanadium flow battery, characterized in that: The invention comprises a porous polybenzimidazole / proton conductor type polyamide composite ion membrane prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
A method for synthesizing high molecular weight polybenzimidazole compounds using microwave-assisted
CN116063679B